Ameliorated New Media Literacy Model Based on an Esthetic Model: The Ability of a College Student Audience to Enter the Field of Digital Art - Xu, Rui; Wang, Chen; Hsu, Yen (Frontiers in Psychology, 2022)
In the current digital environment, people can visit every corner of the world without leaving their homes. New media technology compresses distance and time, but it also subverts the traditional mode of audience presence. Many traditional, offline content expression modes are also moving toward the digital field, and digital art is among them. Digital new media is a new art form that requires its audience to have a new media literacy; this literacy is necessary for aesthetic experience and for audience participation. Empirical research was conducted with an audience of college students. The study had the following purposes: (1) to add a new dimension to the aesthetic model (Silvia 2006, 2013), namely new media literacy, to align the model with the current digital environment, and (2) to test the moderating effect of new media literacy on aesthetic emotion as represented by interest and confusion. The experiment verified the study’s hypothesis that higher new media literacy was associated with higher aesthetic interest and lower confusion. By contrast, lower new media literacy was associated with lower aesthetic interest and higher confusion. New media literacy is an essential quality for contemporary audiences.